Exploring Students' Abductive Reasoning in Solving HOTS Mathematics Problems - Ifana Putri Adelia; Ali Shodikin (LPPM Undiksha, 2026)
Higher Order Thinking Skills (HOTS) in mathematics learning remain a challenge, particularly because students experience difficulties in solving non-routine problems and explaining concepts in depth. In addition, the low level of HOTS is influenced by limitations in the learning process that has not fully developed students’ higher-level reasoning. This study aims to analyze in depth the process of students’ abductive reasoning in solving HOTS-based mathematics problems at each stage of Polya’s problem-solving model. This study employs a qualitative approach with an exploratory descriptive design. The research subjects consisted of 30 tenth-grade students. Data were collected through HOTS-based written tests and semi-structured interviews, with instruments in the form of problem-solving tasks on the topic of Systems of Linear Equations in Two Variables (SLETV) and interview guidelines. Data analysis was conducted using the interactive analysis technique of Miles and Huberman. The results show that students with structured abductive reasoning (undercoded) are more capable of completing all stages of Polya’s model systematically, while students with less appropriate abductive reasoning (overcoded) tend to experience difficulties from the initial stage to reflection. Abductive reasoning is proven to play an important role in helping students develop hypotheses, select strategies, and evaluate solutions more deeply. This study concludes that the quality of abductive reasoning significantly influences students’ success in solving HOTS problems comprehensively. The implications of this study highlight the importance of integrating abductive reasoning into mathematics learning to enhance students’ critical, creative, and reflective thinking skills.